2006
DOI: 10.1021/np060015w
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin as the Active Principle ofHypericumhircinumExerts a Selective Inhibitory Activity against MAO-A:  Extraction, Biological Analysis, and Computational Study

Abstract: The methanol extract from Hypericum hircinum leaves exhibited in vitro inhibition of monoamine oxidases (MAO). Bioassay-guided fractionation led to the isolation of quercetin and five compounds identified for the first time from H. hircinum. Quercetin was the only compound with a selective inhibitory activity against MAO-A, with an IC50 value of 0.010 microM. To explain MAO selective inhibition at the molecular level, a computational study was carried out by conformational search and docking techniques using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(71 citation statements)
references
References 53 publications
5
64
1
Order By: Relevance
“…Lemon balm contains some flavonoids such as quercitrin as well as apigenin and luteolin derivatives that might inhibit monoamine oxidases as previous studies demonstrated that a number of flavonoids possesed MAO-inhibitory activity [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Lemon balm contains some flavonoids such as quercitrin as well as apigenin and luteolin derivatives that might inhibit monoamine oxidases as previous studies demonstrated that a number of flavonoids possesed MAO-inhibitory activity [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the administration of onion powder (50 mg/kg of body weight) prevented this increase in the DOPAC/DA and 5-HIAA/5-HT ratios after the FST trial. The quercetin glycosides present in onion may possess an ability to prevent transmitter turnover by acting as an inhibitor of MAO, as quercetin has been reported to be a selective inhibitor of MAO, 28) resulting in the prevention of transmitter turnover. Nevertheless, this phenomenon was also observed at a dosage of 500 mg of onion powder/kg of body weight, without any decrease in the immobility time in FST.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of both reversible MAO-A inhibitors and selective MAO-B inhibitors are known within the plant kingdom [24]. For example, quercetin is a relatively ubiquitous polyphenol found in many edible plants and has been shown to be a reasonably potent and selective MAO-A inhibitor with an IC 50 of 10 nM [8]. Although quercetin in the aglycone form has limited bioavailability in humans [13,21], its presence in the gut may be sufficient to inhibit gut-derived MAO-A in the creation of a designed synergy with a dietary monoamine.…”
Section: Modulation Of Gut Mao Enzymesmentioning
confidence: 99%